2011
DOI: 10.1186/1824-7288-37-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among Escherichia coli that cause childhood community-acquired urinary tract infections in Northern Italy

Abstract: AbstractsBackgroundResistance rate of Escherichia coli against antimicrobials that are commonly prescribed in pediatric urinary tract infections is currently a matter of concern.MethodsThe antimicrobial susceptibility patterns of uropathogenic Escherichia coli strains to the common antibimcrobials ampicillin, cotrimoxazole, coamoxyclav, ceftazidime, ceftriaxone, nitrofurantoin, and gentamycin were determined in 177 children aged from 2 to 36 months. They presented with their first symptomatic community acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
7
22
2
2
Order By: Relevance
“…In recent years, extended-spectrum β-lactamases (ESBLs) have increased in type and frequency, such as enterobacteriaceae and carbapenemases, which have resulted in a worldwide dissemination of such extended spectrum β-lactamases producing strains [21]; production of extended spectrum β-lactamases (ESBLs) is currently a matter of increasing global concern [5,22]. Ruppe and Cols identified that the occurrence of UTI caused by ESBL E. coli in women who were not exposed to antibiotics was linked to the relative amount of fecal ESBL E. coli [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, extended-spectrum β-lactamases (ESBLs) have increased in type and frequency, such as enterobacteriaceae and carbapenemases, which have resulted in a worldwide dissemination of such extended spectrum β-lactamases producing strains [21]; production of extended spectrum β-lactamases (ESBLs) is currently a matter of increasing global concern [5,22]. Ruppe and Cols identified that the occurrence of UTI caused by ESBL E. coli in women who were not exposed to antibiotics was linked to the relative amount of fecal ESBL E. coli [23].…”
Section: Discussionmentioning
confidence: 99%
“…Because most UTIs are generally treated empirically, the selection of antimicrobial agent should be determined not only by the most common pathogen, but also from consideration of risk factors that may alter that pathogen´s typical susceptibility profile. One such risk factor is the production of extended spectrum beta lactamases [5,7]. The acquisition of such beta lactamases may be related to changes in the bacterial genome by mutation or acquisition by horizontal transfer of extrachromosomal genetic material [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite extensive use of FM for many years, this antibiotic still possesses an excellent activity against urinary isolates of E. coli (6,7,11,16,17,19); however, compared with fluoroquinolones, the FM is associated with lower treated rates and more side effects in the treatment of acute cystitis (11,18); also, this antibiotic was poorly tolerated by children and old patients and cannot be used for pyelonephritis (5). In our study, after FM, the E. coli isolates were showing the least resistance to CTX.…”
Section: Discussionmentioning
confidence: 99%